Detection of Aspergillus fumigatus in Hordeum vulgare marked at Morelia, Mich, México with potential to synthetize ochratoxin A - Liliana Márquez-Benavides; Blanca Celeste Saucedo-Martínez; Juan Manuel Sánchez-Yáñez (Journal of the Selva Andina Research Society)
The grains of Hordeum vulgare or Hv (barley) marketed in the city of Morelia, Michoacán, Mexico as food or beverage (craft beer) for humans and animals, can be contaminated with propagules of Aspergillus. When Hv is grown through an intensive agricultural system, based on the application of chemical fertilizers and pesticides. The Hv grains transported, stored and marketed under inappropriate conditions in Morelia, allow the growth of Aspergillus genera and species that potentially synthesize mycotoxins such as ochratoxin A. The objectives of this research were i) to analyze the density of Aspergillus in grains of Hv, commercialized in Morelia, Mich, Mexico, ii) Demonstrate the potential capacity of A. fumigatus isolated from Hv in Sabouraud dextrose agar (SDA) to synthesize ochratoxin A. Therefore, Hv grains collected in Morelia, Mich was used to determine the density and diversity of Aspergillus species. As the potential capacity of the main species isolated: A. fumigatus in SDA for the synthesis of ochratoxin A was analyzed without no problem since chemical composition of SDA was enough for nutritional demand for A. fumigatus. All experimental data were analyzed by ANOVA/Tukey. The results indicate a relatively high number of propagules of A. fumigatus that contaminate the grains of Hv commercialized in Morelia, where 67 % of the isolates of A. fumigatus showed the potential to synthesize ochratoxin A in SDA. It is concluded that there is an evident risk for humans and animals that consume barley (Hv) contaminated by A. fumigatus that potentially generate ochratoxin A, for which health care is required in the handling and commercialization of Hv, in Morelia City.